Belén de Sárraga and the Brasilian Freemansory - 1911 - Lotúmolo Junior, José (2025)
This article demonstrates the role of Brazilian Masonic Lodges in supporting the trips by the Spanish lecturer and Freethinking Belén de Sárraga, in Brazil in 1911. Documentary Research in newspapers and magazines of the time demonstrated the existence of a communication network of Masonic Order in Brazil to explain how Belén traveled to more than 36 cities, giving her lectures in packed theaters, railway stations and with an itinerary that suffered no interruption, confirming that Freemasonry was indeed engaged in the project of dissemination of Free-Thought, through the support for Belén de Sárraga’s visit to Brazil in 1911.